Editorial: Bioinformatics and systems biology strategies in disease management with a special emphasis on cancer, Alzheimer’s disease and aging - Singh, Tiratha Raj; Vannier, Brigitte; Singh, Ragini Raj; Yadav, Hari Om; Fröhlich, Holger (Frontiers in Molecular Biosciences, 2025)
Graphical AbstractBioinformatics and systems biology strategies for managing cancer and Alzheimer's disease. Key concepts include multi-omics data, computational modeling, network analysis, and nanotechnology. Translational applications cover diagnostics, prognostics, and therapeutics. Arrows suggest a circular process between concepts and applications.